Timing and Predictors of Upper Extremity Peripheral Nerve Reconstruction - Kelsey M. Gray; Andrzej J. Burkat; Lucas A. Arney; Nicholas J. Peterman; Sahith R. Mandala; Anthony E. Capito (JPRAS Open)
SUMMARY/ABSTRACT: Primary neurorrhaphy is the preferred reconstruction modality over nerve grafting, especially for motor nerves. The main limitation to primary repair is often dictated by tension secondary to increased nerve defect length. A retrospective review was conducted on sharp transections of mixed motor and purely sensory nerves in the upper extremity to assess factors influencing defect length. Two groups of either primary repair or nerve graft/conduit were created for comparison. Overall, 71 injured mixed motor nerves and 224 injured sensory nerves were included in the analysis. There were no significant differences in patient demographics between the groups. The primary repair group had a significantly shorter time interval between injury and surgical fixation when compared to the conduit/graft group. Conduit or graft technique was associated with a significantly larger tissue gap after preparation of the nerve ends. Our data suggest that the optimal time for primary repair is within 3 days after injury for mixed nerves and within 7 days for purely sensory nerves. A total of 167 nerve reconstructions were included in a random forest plot, which demonstrated nerve defect size to be influenced by days from injury, type of nerve injured, age, and hypertension. A publicly available 4-feature calculator, nerve evaluation and retraction variability estimator—NERVE, was developed from the forest plot to predict a patient's nerve deficit of ± 3.78 mm on an average, R2=0.89. This calculator could aid surgeons with surgical planning by estimating the potential need of grafts or conduits for reconstruction.